Nanoplatforms for Sepsis Management: Rapid Detection/Warning, Pathogen Elimination and Restoring Immune Homeostasis - Luo, Gan; Zhang, Jue; Sun, Yaqi; Wang, Ya; Wang, Hanbin; Cheng, Baoli; Shu, Qiang; Fang, Xiangming (Nano-Micro Letters, 2021)
Sepsis, a highly life-threatening organ dysfunction caused by uncontrollable immune responses to infection, is a leading contributor to mortality in intensive care units. Sepsis-related deaths have been reported to account for 19.7% of all global deaths. However, no effective and specific therapeutic for clinical sepsis management is available due to the complex pathogenesis. Concurrently eliminating infections and restoring immune homeostasis are regarded as the core strategies to manage sepsis. Sophisticated nanoplatforms guided by supramolecular and medicinal chemistry, targeting infection and/or imbalanced immune responses, have emerged as potent tools to combat sepsis by supporting more accurate diagnosis and precision treatment. Nanoplatforms can overcome the barriers faced by clinical strategies, including delayed diagnosis, drug resistance and incapacity to manage immune disorders. Here, we present a comprehensive review highlighting the pathogenetic characteristics of sepsis and future therapeutic concepts, summarizing the progress of these well-designed nanoplatforms in sepsis management and discussing the ongoing challenges and perspectives regarding future potential therapies. Based on these state-of-the-art studies, this review will advance multidisciplinary collaboration and drive clinical translation to remedy sepsis. Highlights: 1 This review highlights pathogenesis and clinical challenges of sepsis. 2 Advantages of different types of nanoplatforms are presented, and the rationality of nanoplatforms in sepsis management is analyzed. 3 Advances of nanoplatforms in diagnosis and therapy of sepsis are systematically summarized, and ongoing challenges and future perspectives are discussed.